2021
DOI: 10.1001/jamanetworkopen.2021.22818
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Medication Regimens for Children With Neurological Impairment

Abstract: IMPORTANCE Parents of children with severe neurological impairment (SNI) manage complex medication regimens (CMRs) at home, and clinicians can help support parents and simplify CMRs.OBJECTIVE To measure the complexity and potentially modifiable aspects of CMRs using the Medication Regimen Complexity Index (MRCI) and to examine the association between MRCI scores and subsequent acute visits. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study was conducted between April 1, 2019, and December 31, 2020, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…In addition, our results also suggested that poor health and increased healthcare utilisation were significantly and positively associated with polypharmacy. Although few studies evaluated outpatient polypharmacy in children with asthma, this finding aligns with a recent study by Feinstein et al suggesting medication regimen complexity is associated with increased acute visits among children with neurological impairment 37. Our results are also similar to the risk factors of polypharmacy among adults including multiple commodities and seeing multiple medical providers 38.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, our results also suggested that poor health and increased healthcare utilisation were significantly and positively associated with polypharmacy. Although few studies evaluated outpatient polypharmacy in children with asthma, this finding aligns with a recent study by Feinstein et al suggesting medication regimen complexity is associated with increased acute visits among children with neurological impairment 37. Our results are also similar to the risk factors of polypharmacy among adults including multiple commodities and seeing multiple medical providers 38.…”
Section: Discussionsupporting
confidence: 91%
“…Although few studies evaluated outpatient polypharmacy in children with asthma, this finding aligns with a recent study by Feinstein et al suggesting medication regimen complexity is associated with increased acute visits among children with neurological impairment. 37 Our results are also similar to the risk factors of polypharmacy among adults including multiple commodities and seeing multiple medical providers. 38 Furthermore, another cross-sectional study suggested that adults with respiratory conditions had a lower prevalence of polypharmacy compared with other chronic condition groups, but prevalence increased as the number of comorbidities increased, including musculoskeletal or cardiometabolic diseases.…”
Section: Risk Factors For Polypharmacy Among Children With Asthmasupporting
confidence: 80%
“…5,28 PGx data can also provide insight into drug-drug interactions, a common concern in polypharmacy. 29 The prevalence of polypharmacy in this study cohort was comparable to adults with psychiatric illness and the elderly, populations where PGx profiling is most common and best established. 30 As expected, PGx variants were as common in CMC as they are in the general population.…”
Section: Cmc Are a Priority Population For Trialing Genotype-guided P...mentioning
confidence: 60%
“…Feinstein and colleagues used a Medication Regimen Complexity Index (MRCI), comprised of 3 sub-scores for dosage form, dose frequency, and specialized instructions, to identify potentially modifiable factors associated with suboptimal therapies. They found a median (IQR) of 6 (4-7) dosage forms per patient, 7 (5-9) dose frequencies per patient, and 5 (4-8) instructions per patient, with significantly higher counts among higher MRCI groups [23]. Feinstein and Orth discussed provider-and system-level recommendations to improve medication safety in CSHCN-CMC [67].…”
Section: Discussionmentioning
confidence: 99%
“…CSHCN-CMC often are administered multiple medications, many of which are liquid compounded nonsterile preparations (pCNSPs) [16,17]. Assuring continuity of care at care transitions for safe medication management has been identified as an often-daunting task for parents, caregivers, and the patient's healthcare team [18][19][20][21][22][23][24][25][26][27]. Suggestions for implementing, sustaining, and improving medication management have been forwarded in order to encourage development of a child-friendly medication use system, including…”
Section: Introduction and Statement Of The Problemmentioning
confidence: 99%